Risk factors for recurrent ectopic pregnancy: a case–control study. (14th September 2016) - Zhang, D; Shi, W; Li, C; Yuan, J‐J; Xia, W; Xue, R‐H; Sun, J; Zhang, J
Abstract : Objective: To study the risk factors for recurrent ectopic pregnancy (REP). Design: A retrospective case–control study. Setting: A university medical centre. Population: 554 women with a history of ectopic pregnancy (EP) were included. Among them were 181 women with current EP, 184 women with current intrauterine pregnancy (IUP) and 189 nonpregnant women (NonP). Methods: The three groups were matched at a ratio of 1:1 with respect to current age, age of initial EP and gestational week of initial EP. Socio‐demographic characteristics, reproductive history, gynaecological and surgical history, and experience of contraception were compared among the three groups. A multivariable logistic regression analysis was used to adjust for confounders and calculate adjusted odds ratios (AORs). Results: The risk of REP increased with history of infertility (AOR = 3.84, 95%CI 2.16–6.86) in REP women compared with IUP controls. Compared with NonP controls, salpingotomy (AOR = 3.04, 95%CI 1.21–36.51) for previous EP was a risk factor for REP. Multiparous women were less likely to suffer REP when compared with NonP women (AOR = 0.36, 95%CI 0.18–0.62) or IUP controls (AOR = 0.35, 95%CI 0.20–0.62). Current use of an intrauterine device (IUD) (REP versus NonP, AOR = 0.02, 95%CI 0.00–0.08) or condoms (REP versus NonP, AOR = 0.16, 95%CI 0.07–0.38) significantly reduced the risk of REP compared with those not using any contraception. Similarly, previous use of condoms also prevented REP compared with those with no previous condom use (REP versus NonP, AOR = 0.20, 95%CI 0.08–0.49; REP versus IUP, AOR = 0.40, 95%CI 0.22–0.71). Conclusions: Women with history of infertility or salpingotomy should be alert for the recurrence of EP. Multiparous women are less likely to suffer REP. We propose the use of condoms for effective prevention of REP. Tweetable abstract: History of infertility and salpingotomy for last EP are risk factors for recurrent EP. Tweetable abstract: History of infertility and salpingotomy for last EP are risk factors for recurrent EP.